2013
DOI: 10.1128/aac.00603-13
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Pantothenamides with Vanin Inhibitors as a Novel Antibiotic Strategy against Gram-Positive Bacteria

Abstract: eThe emergence of resistance against current antibiotics calls for the development of new compounds to treat infectious diseases. Synthetic pantothenamides are pantothenate analogs that possess broad-spectrum antibacterial activity in vitro in minimal media. Pantothenamides were shown to be substrates of the bacterial coenzyme A (CoA) biosynthetic pathway, causing cellular CoA depletion and interference with fatty acid synthesis. In spite of their potential use and selectivity for bacterial metabolic routes, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 29 publications
0
43
0
Order By: Relevance
“…Excretion of pantothenic acid occurs mostly in the urine, as free pantothenic acid and some 4'-phosphopanthenate, however 15% of pantothenic acid is also oxidized and excreted through the lungs as CO2. Several studies to date have reported that amides derived from pantothenic acid possess an antibiotic quality within the body, which may prove to be a novel antibiotic solution to appropriately relevant gram positive bacteria [92] or malarial agents [93]. Higher levels of nutrient intake, including pantothenic acid, results in better mental health scores, as based on the global assessment of functioning scores and the Hamilton depression rating scale [39].…”
Section: Vitamin B5 (Pantothenic Acid)mentioning
confidence: 99%
“…Excretion of pantothenic acid occurs mostly in the urine, as free pantothenic acid and some 4'-phosphopanthenate, however 15% of pantothenic acid is also oxidized and excreted through the lungs as CO2. Several studies to date have reported that amides derived from pantothenic acid possess an antibiotic quality within the body, which may prove to be a novel antibiotic solution to appropriately relevant gram positive bacteria [92] or malarial agents [93]. Higher levels of nutrient intake, including pantothenic acid, results in better mental health scores, as based on the global assessment of functioning scores and the Hamilton depression rating scale [39].…”
Section: Vitamin B5 (Pantothenic Acid)mentioning
confidence: 99%
“…Many pantothenamides tested to date are degraded by the enzyme pantetheinase (vanin) [41,46,49,50] into pantothenate and the corresponding amine (blue shading), and thereby rendered ineffective as pantothenate antivitamins [41,49,50].…”
Section: Figure 3 Pantetheinase-mediated Degradation Of Pantothenamidmentioning
confidence: 99%
“…Two strategies have been put forward to overcome this pantetheinase-mediated degradation and thus enable the pantothenamides to exert their antimicrobial effect: (i) inhibition of pantetheinases by potent and specific inhibitors, such as compound RR6 (purple shading) [50], and (ii) modification of the pantothenamide core structure to render the compounds resistant to degradation while maintaining their antimicrobial activity (green shading) [49]. Both strategies appear to be effective in vitro and both offer distinct advantages and disadvantages.…”
Section: Figure 3 Pantetheinase-mediated Degradation Of Pantothenamidmentioning
confidence: 99%
See 2 more Smart Citations